'Leaving the red Tories': Ideology, leaders, and why party members quit. (January 2022) - Barnfield, Matthew; Bale, Tim
What little research exists on why party members quit has tended to find that exit is driven primarily by political and ideological concerns. This research note builds on this, framing this finding theoretically and arguing that such theory should allow for the role of negative triggers – events that cause people to quit. We focus on the example of changes of leadership. Using data from four Party Members Project surveys, we find that British party members seem to leave parties mainly for political and ideological reasons, and because of disillusionment or disagreement with their leaders. This disillusionment, in turn, is often based on perceived ideological differences. We illustrate this with tweets by Labour members cancelling (or considering cancelling) their membership in the immediate wake of the election of Keir Starmer as party leader in April 2020.